2021
DOI: 10.20961/stjssa.v18i2.56330
|View full text |Cite
|
Sign up to set email alerts
|

Rice-husk biochar effects on organic carbon, aggregate stability and nitrogen-fertility of coarse-textured Ultisols evaluated using Celosia argentea growth

Abstract: There are insufficient data supporting the enormous potential of biochar in highly weathered tropical soils. This glasshouse study assessed rice-husk biochar (RHB) effects on soil organic carbon, aggregate stability and nitrogen fertility of sandy-loam Ultisols which were evaluated using spinach (<em>Celosia argentea</em>) growth. Five RHB rates 0, 5, 10, 20, and 40 g per two-kg-soil (0, 7.5, 15, 30 and 60 t ha<sup>−1</sup>, respectively) were studied under 0, 4, 8, and 12 weeks of incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Introducing biochar such as rice husks can increase the organic carbon content in the soil. Increasing the dose of biochar positively correlates with the organic carbon content (Ebido et al, 2021). Therefore, it is best to use biochar at the beginning and post-harvest of tillage.…”
Section: Source: Compiled By the Authors Of This Study Based On Data ...mentioning
confidence: 99%
“…Introducing biochar such as rice husks can increase the organic carbon content in the soil. Increasing the dose of biochar positively correlates with the organic carbon content (Ebido et al, 2021). Therefore, it is best to use biochar at the beginning and post-harvest of tillage.…”
Section: Source: Compiled By the Authors Of This Study Based On Data ...mentioning
confidence: 99%
“…In Enugu State, Nigeria, Ebido et al [186] conducted a study investigating the impacts of rice-husk BC pyrolyzed at 550-600 • C on organic carbon, aggregate stability, and the nitrogen fertility of coarse-textured Ultisols. They observed that as the rate of rice-husk BC increased, soil organic carbon and aggregate stability also increased.…”
Section: A Case Study Of Recent Studies Of Biochar In Nigeriamentioning
confidence: 99%
“…As the rate of rice-husk-biochar (BC) application rose, there was a corresponding increase in soil organic carbon content and improvement in aggregate stability [186] ---Abia HF BC + poultry manure Significant improvement in soil chemical characteristics and the yield of fresh ginger rhizomes [187] Softwood prune branches -Nasarawa DS BC + supplemental micronutrient Okra vegetative-growth parameters increased with the application of both BC and micronutrients with no significant difference. Increased soil percentage of organic carbon, organic material, cation exchange capacity, nitrogen content, and pH levels [188] * SLS Sahel savanna, SS Sudan savanna, NGS Northern Guinea savanna, SGS Southern Guinea savanna, MA mid-altitude, DS derived savanna, HF humid forest.…”
Section: A Case Study Of Recent Studies Of Biochar In Nigeriamentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, several studies on the effect of biochar singularly have been carried out, including on the P-availability (Zhang et al, 2022), improvement of soil physical properties (Aslam et al, 2014;Yin et al, 2018), chemical properties of the soil (Bista et al, 2019), some soil characteristics (Yadav et al, 2018), soil aggregate stability (Ebido et al, 2021) and to the development of rice roots (Kartika et al, 2021). However, no research has been found on how the role of biochar was given together with other organic amendments in acid sulphate soil.…”
Section: Introductionmentioning
confidence: 99%